Pemanfaatan Permainan Tradisional Congklak Sebagai Media Interaktif Dalam Pembelajaran FPB Dan KPK Di SDN 2 Kragilan - Andi Mufti Mubarak Asmar; Naimah Parondah; Aspikal Aspikal (Abdimas Mandalika, 2026)
Abstract:  The congklak game is highly effective in mathematics instruction at the elementary school level. Observations at SDN 2 Kragilan revealed that educators and mathematics teachers at the school still rely on conventional methods in their teaching. Furthermore, the use of learning media remains limited or lacks innovation when teaching the KPK and FPB concepts. The objective of this Community Service Program (PKM) is to provide an analysis regarding the introduction of the traditional congklak game as a learning medium for teaching the KPK and FPB at SDN 2 Kragilan. The program was implemented using a qualitative research methodology. The results of the PKM activity show that introducing traditional games as a learning medium can effectively improve students’ learning outcomes in KPK and FPB at SDN 2 Kragilan. Teachers’ innovations in learning media need not be limited to modern games; traditional media such as the congklak game can also be used to introduce KPK and FPB concepts. The congklak game can also foster hard work, a sense of achievement, and perseverance.Abstrak: Permainan congklak memiliki keefektifan yang baik dalam kegiatan pembelajaran matematika pada jenjang Sekolah Dasar. Hasil observasi di SDN 2 Kragilan memaparkan bahwa pendidik atau guru matematika di SDN 2 Kragilan masih menggunakan metode konvensional dalam kegiatan pembelajaran. Selain itu, penggunaan dari media pembelajaran juga masih minim digunakan ataupun kurang inovatif pada materi KPK dan FPB. Tujuan dari PKM ini adalah memberikan hasil analisis terkait dengan pengenalan permainan tradisional congklak sebagai media pembelajaran matematikan FPB dan KPK di SDN 2 Kragilan. Pelaksanaan pengabdian menggunakan penulisan metode kualitatif. Hasil kegiatan PKM ialah pengenalan permainan tradisional sebagai salah satu media pembelajaran mampu memberikan keefektifan dalam peningkatan hasil belajar siswa materi KPK dan FPB di SDN 2 Kragilan. Inovasi guru dalam media pembelajaran tidak hanya berbasis permainan modern. Namun, penggunaan dari media tradisional seperti permainan congklak juga dapat digunakan sebagai media pengenalan materi KPK dan FPB. Permainan congklak juga dapat mengembangkan perilaku kerja keras, penghargaan, dan ketekunan.